(untitled) (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
This study is expected to give useful information about The Use of L1 in Teaching English to Young Learners at Elementary School. From the information given, the English teacher can evaluate whether the use of L1 in Teaching English to Young Learners at Elementary School. In addition, the result of this research can be used as a reference for further researcher who is interested in conducting similar study. The research design of this study was qualitative research. The research method used a qualitative approach to describe English classroom management, application and response used by the teacher. Data collection techniques are: observation and interview. Analytical techniques are: data reduction, data display, and conclusion. The subjects of this study was English teacher. Based on the result of the research, the teacher had some roles of L1 in Teaching English to Young Learners at Elementary School. Then, the roles helped the English teacher in Teaching English to Young Learners at Elementary School. Key wards: First Language (L1), Roles of L1.